2012
DOI: 10.1155/2012/242875
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Physical Activity, Weight Status, and Culture in a Sample of Children from the Developing World

Abstract: Objective. Barbados, a small developing state at the end of the nutrition transition, faces an obesity epidemic. Although there is hope of stemming the epidemic in childhood, no descriptions of children's dietary and physical activity (PA) patterns are available for planning purposes. We describe the food and activity preferences and adult encouragement of active and sedentary behaviors for children 9–11 years in relation to weight status and the cultural context. Design. We used data from a pilot study preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
3
8
0
1
Order By: Relevance
“…Furthermore, snacking of locally made processed foods was common among the children. To our knowledge, this is the first published study documenting the wide consumption of SBs in such a Malawian population and has comparable results to studies that have been conducted elsewhere [4][5][6][7][8][9][10][11][12][13] . The study provides a basis for future, more comprehensive studies in Malawi on SBs, which will help in designing interventions to curb childhood obesity.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, snacking of locally made processed foods was common among the children. To our knowledge, this is the first published study documenting the wide consumption of SBs in such a Malawian population and has comparable results to studies that have been conducted elsewhere [4][5][6][7][8][9][10][11][12][13] . The study provides a basis for future, more comprehensive studies in Malawi on SBs, which will help in designing interventions to curb childhood obesity.…”
Section: Discussionsupporting
confidence: 61%
“…Overweight children, just like adults, are at high risk of a wide range of health problems, including cardiovascular diseases and diabetes 2,3 . By significantly contributing to total energy intake 4 , consumption of sugar-sweetened beverages (SBs), such as carbonated soft drinks and flavoured juice drinks, has been linked to the rise in obesity and abdominal obesity among children [5][6][7] . High consumption of SBs also reduces micronutrient intake owing to a dilution effect 8 , thereby increasing the risk of micronutrient deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one-fourth of non-Hispanic White children aged 2–5 are overweight (i.e., >85 percentile of sex-based weight-for-length), whereas over one-third of Mexican American children in the same age group are overweight [1]. Although a portion of this disparity is likely attributed to socioeconomic conditions such as food insecurity [25], cultural beliefs about the proximal antecedents to obesity also contribute to ethnic variation in childhood overweight and obesity [6, 7]. …”
mentioning
confidence: 99%
“…A recent study in the United Kingdom with ethnic minority children also revealed that parent´s conversations about physical activity were limited, and identified the lack of knowledge of physical activity guidelines for children as a possible barrier [23]. Lack of parental encouragement to play active games has also been noted in other LMIC [24]. …”
Section: Discussionmentioning
confidence: 99%